Properties of chitosan/soy protein blended films with added plasticizing agent as a function of solvent type at acidic pH. Issue 1 (2nd January 2016) - Boy, Ramiz; Maness, Chandler; Kotek, Richard
ABSTRACT: Pure and blend films from chitosan (CH) and soy protein isolate (SPI) were produced in varying compositions (CH/SPI 75/25, 50/50, 25/75 w/w) based on the solvent type (acetic and formic acids). Glycerol was used as a plasticizer. The interactions between the two biopolymers was confirmed by FTIR and TGA, indicating miscibility and compatibility. Increasing the amount of soy protein decreased the tensile strength and absorptive properties, but improved the ability of the film to withstand thermal degradation. Blend films cast using acetic acid gave higher hydrophobicity, better internal blend miscibility, and better tensile properties than blend films cast from formic acid. GRAPHICAL ABSTRACT: